Problems and Strategies in Translating Legal Texts - Rudy Sofyan; Rusdi Noor Rosa (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
Translating legal texts is considered as the most difficult translation task as it needs accurate and correct translation, and even minor errors can result in lawsuits and legal exposure. This paper aims at finding out the translation problems and formulating the strategies best applicable in translating legal texts from bahasa Indonesia into English. This is a descriptive study using a document analysis as the method. The data were 15 legal texts having been translated from bahasa Indonesia into English by semi-professional translators. In analysing the data, the document analysis was carried out by skimming, reading, and interpreting the translated legal texts. The results of data analysis reveal three general problems in translating legal texts done by the semi-professional translators, including finding the right equivalent, translator’s insufficient knowledge of English legal language and source text decoding. To overcome such problems, four strategies are proposed: (i) utilizing online resources, (ii) finding the proposition of the legal sentence, (iii) using a description technique, and (iv) employing functional approach to translation. It is concluded that translating legal texts requires translator’s good knowledge of applicable laws and language competence in both the source language and target language.